2011
DOI: 10.5732/cjc.011.10174
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight alters the gene expression profile of cervical cancer cells

Abstract: Our previous study revealed that spaceflight induced biological changes in human cervical carcinoma Caski cells. Here, we report that 48A9 cells, which were subcloned from Caski cells, experienced significant growth suppression and exhibited low tumorigenic ability after spaceflight. To further understand the potential mechanism at the transcriptional level, we compared gene expression between 48A9 cells and ground control Caski cells with suppression subtractive hybridization (SSH) and reverse Northern blotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Cis and trans regulatory factors for the localization of the MALAT-1 lncRNA to nuclear speckles have been identified [ 47 ]. Functional studies performed on cell lines from different types of human malignancies revealed that MALAT-1 is indeed key for the maintenance of hyperproliferation and metastasizing potential [ 26 , 34 , 56 , 69 , 76 , 77 , 81 , 83 ]. In addition to being a promising biomarker for the diagnosis of a wide range of human malignancies, MALAT-1 proved to be a putative target for siRNA-mediated therapy, as recently demonstrated by Ren et al [ 54 ].…”
Section: The Great Past and Bright Future Of Lncrnas Unexpectedly Idementioning
confidence: 99%
“…Cis and trans regulatory factors for the localization of the MALAT-1 lncRNA to nuclear speckles have been identified [ 47 ]. Functional studies performed on cell lines from different types of human malignancies revealed that MALAT-1 is indeed key for the maintenance of hyperproliferation and metastasizing potential [ 26 , 34 , 56 , 69 , 76 , 77 , 81 , 83 ]. In addition to being a promising biomarker for the diagnosis of a wide range of human malignancies, MALAT-1 proved to be a putative target for siRNA-mediated therapy, as recently demonstrated by Ren et al [ 54 ].…”
Section: The Great Past and Bright Future Of Lncrnas Unexpectedly Idementioning
confidence: 99%
“…It is significantly enriched in ribosome function and neoplasm ( 35 , 36 ). MYL6 is an ATPase cellular motor protein that is highly expressed in obesity, asthma, and cervical cancer, but the potential mechanisms are not fully known ( 37 , 38 ). These findings suggest that dysfunctions in inflammatory response, neuron apoptosis, autophagy, and the endoplasmic reticulum might participate in the MS pathology, speculation that should be validated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Microgravity can be exploited to study biological mechanisms and pathways to improve our understanding of many diseases, including cancer. Previous spaceflight experiments have shown that exposure to the space environment alters immune cell growth and function [11], causes cytoskeleton and cell shape changes [12], and alters cellular gene expression including genes involved in replication and suppression of tumors [13,14]. This brings us to our second Tumors in Space hypothesis.…”
Section: The Problem Statement and Supporting Evidencementioning
confidence: 98%